On the impossibility to back home or written as possible place back to the future - Marandola Jr., Eduardo (Geografares, 2016)
Meditation on the meaning of the possible place, writing, and thinking back to the future, the text is as experience, composted by literary interstices of the geographical- -political compose of the geometries of thought